Generation, propagation and dissipation of internal tides on the continental shelf and slope off the west coast of India. (1st February 2021) - Subeesh, M.P.; Unnikrishnan, A.S.; Francis, P.A.
Abstract: The present study focuses on the dynamics of M2 internal tides on the shelf and slope off the west coast of India (WCI) using a high-resolution (1/48 ∘ ) numerical ocean circulation model configured for the eastern Arabian Sea. The WCI is characterized by the presence of large internal tides where most of the internal tides generated on shelf-slope regions propagate offshore as beams. Baroclinic energy budget estimates show that about 2.4 GW of barotropic tides gets converted to baroclinic tides over the region. The regions of shelf breaks and upper slope around 16–18.5 ∘ N and the northern part of the Chagos-Laccadive Ridge (8–14 ∘ N) are the two most important regions of internal tide generation along the WCI, which together contribute to more than 50% of total area-integrated M2 conversion over the domain. The diapycnal diffusivity for internal tide dissipation exceeds 10 −3 m 2 / s in these regions. The central and northern slope regions off the WCI are dominated by locally generated internal tides, whereas part of internal tides in the southern region is characterized by the presence of remotely-generated internal tides coming from the Chagos-Laccadive Islands. Internal tides experience significant seasonal variation on the shelf owing to the variation in stratification, while their variations are negligible on the slope, where the seasonal variation in stratification is not significant. Highlights: Numerical simulation of internal tides on the shelf-slope region off west coast of India show large spatio-temporal variabilities. The total barotropic to baroclinic conversion of M2 tidal constituent is about 2.4 GW. The two most important internal tide generation sites are shelf break and slope along 16°–18.5° N and Chagos-Laccadive Ridge. Vertical mixing in the region is significantly contributed by internal tides.